1998
DOI: 10.1111/j.1399-6576.1998.tb05106.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo spasmolytic effect of ketamine and adrenaline on histamine‐induced airway constriction

Abstract: We have found that K could reverse the H-induced bronchoconstriction and potentiate the A-induced bronchial relaxation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…We anesthetized the patient with propofol, fentanyl and ketamine. Propofol (7) and ketamine (8) have been reported to produce bronchodilation. Although the use of fentanyl for asthmatic patients is controversial, Zappi and colleagues (9) reported that opioids relax airway smooth muscles via μ‐opioid receptors.…”
Section: Discussionmentioning
confidence: 99%
“…We anesthetized the patient with propofol, fentanyl and ketamine. Propofol (7) and ketamine (8) have been reported to produce bronchodilation. Although the use of fentanyl for asthmatic patients is controversial, Zappi and colleagues (9) reported that opioids relax airway smooth muscles via μ‐opioid receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine, adrenaline, isoflurane, theophylline and salbutamol have been used in the management of bronchospasm as they all have bronchodilatatory properties in both human beings and dogs [8][9][10][11][12][13][14][15][16][17] . None of these treatments showed clear and complete resolution of the clinical signs and it is not possible to clearly associate the success of the treatment to one specific drug; most likely their combination led to the resolution of clinical symptoms.…”
Section: Treatmentmentioning
confidence: 99%
“…52 Specifically in pediatric patients, ketamine can provide sedation safely in those with asthma who require noninvasive mechanical ventilation with minimal respiratory depression and promotion of bronchodilation. 53 In these same patients who require intubation, ketamine has been shown to be safe and efficacious as an induction agent for intubation of critically ill patients. 54,55 Subhypnotic doses of ketamine administered by continuous infusion have been used for patients in the ICU to decrease total required opioid and other sedative doses.…”
Section: Ketaminementioning
confidence: 99%